Staged and non staged anaerobic filters : microbial selection, hydrodynamic aspects and performance - Alves, M. M. (1997)
This work reports on the study of a staged and a non staged anaerobic filter treating a synthetic dairy waste under similar operating conditions. The effect of increasing the substrate concentration from 3 to 12 g COD/l at a constant hydraulic residence time (HRT) of 2 days was evaluated with respect to overall reactor performance, gas production and volatile fatty acids profiles along the height. The potential maximum specific methanogenic activity against acetate, H2/CO2, two indirect substrates (propionate and butyrate) and the lactose specific activity were determined for sludge sampled from three different points in each reactor, under two operating conditions (influent COD of 3 and 9 g COD/l). Although all microbial phases of anaerobic process were found throughout the reactors, it was possible to identify different specific sludges at different heights in both reactors. The pressure transducer technique applied was proven to be a reliable method to study methanogenic activity of different trophic groups in consortia. Performances of the two configurations were very similar under the operating conditions tested and the plug flow behaviour of the staged reactor was clearly reduced when the influent concentration increased from 3 to 9 g COD/l.